Geography of gender in the third world - Momsen, Janet Henshall; Townsend, Janet G. (University of New York Press, 1987)
This pioneering book addresses a key issue in development studies. It follows the influential 'Geography and Gender' as the second collaborative work generated by the Women in Geography Study Groups of the Institute of British Geographers. Its twenty substantive papers explore spatial patterns of gender in Asia, Africa, the caribbean and Latin America. The book's contributors come from Europe, North and South America, India, Sri Lanka, Malaysia, Thailand, Egypt and the Caribbean. 'Geography of Gender in the Third World' analyses the position of women and the societies that ignore and exploit them. it provides both substantial original research and a comprehensive introduction to the geography of gender in low income countries. The book makes a powerful claim for the regional geography of gender.
Keywords: 1900-1999; afrique; amériques; asie; fem1000; genre; identités LGBTQIA2+; premier cycle; périodes historiques; régions géographiques; sud global; thématiques